Analysis of the Liability of Perpetrators of Fraud via BRI Link Transfer (Decision Study Number: 14/Pid.B/2023/PN Bbu) - Zulfi Diane Zaini; Adellia Patricia Chandra (CV. Rayyan Dwi Bharata, 2024)
Accountability of perpetrators of criminal acts is a relevant study in the context of justice and law enforcement. This research illustrates how perpetrators of fraud can be faced with accountability and their actions. Look for various legal approaches and sanctions that can be implemented to ensure that perpetrators of fraud receive appropriate consequences. Accountability for perpetrators of criminal acts is also discussed as part of efforts to create a just and effective legal system. There are factors that influence individuals to be involved in criminal acts. In-depth analysis of social, economic, and psychological dynamics provides insight into behavioral patterns that can be used to prevent and treat crime. In addition, this article highlights the importance of rehabilitation and prevention approaches to change the direction of criminal behavior towards positive reintegration in society. Policy implications and preventive actions are also discussed to create a safer and more just environment. Crime is a complex phenomenon that affects social stability and community security.